A COST VARIATION ANALYSIS STUDY OF DRUGS USED IN THE MANAGEMENT OF BENIGN PROSTATIC HYPERPLASIA AVAILABLE IN THE INDIAN MARKET - RANI, VIBHA; VENEPALLY, SAILAXMI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objectives of the study are to evaluate the cost variation and cost ratio of different brands of the drugs used in the treatment of benign prostatic hyperplasia (BPH). Methods: The cost of alpha-blockers and 5 alpha-reductase inhibitors used in the treatment of BPH was noted from CIMS (Oct 2019–Jan 2020), Drugs Update, and Medline. The differences between the maximum and minimum cost of various brands of the same drug were analyzed and percentage variation in the cost was calculated. The results of the study were expressed in absolute numbers and percentages. Results: All the drugs used in the treatment of BPH are only available in tablet and capsule forms, in 10 different dosages and in 242 different brand names, of which 10 mg alfuzosin and 2.5 mg finasteride have the highest (518) and lowest (14) percentage of cost variation, while 0.4 mg tablet form of tamsulosin is available in the maximum number of brands-41. Conclusion: This pharmacoeconomic study reveals that there is wide variation in the cost of most of the drugs used in the treatment of BPH. Therefore, it is very much essential for both government and pharmaceutical companies to make combined efforts to reduce the cost of these drugs, which will reduce the economic burden on the patients and also reduce the overall health care costs.